Spathiphyllum frailescanense (Araceae), a new species from Sierra Madre of Chiapas, Mexico - J.-Pérez, A. Fabian; Pérez-Farrera, Miguel Ángel; Díaz Jiménez, Pedro; Martínez-Martínez, Mauricio Gerónimo (Phytotaxa, 2023)
During fieldwork conducted between 2020 and 2022 in the Sierra Madre of Chiapas, we discovered a previously undescribed species of Spathiphyllum. It is morphologically similar to S. matudae, but differs in having shorter petioles, lanceolate or elliptic-lanceolate blades, sometimes subovate, fewer pairs of primary veins per side, stipitate spadix and its pistils constricted between the ovary and the style. Here, we describe and illustrate S. frailescanense, a new species of Araceae from the Sierra Madre de Chiapas, Mexico.